Building Trust and Collaborating with Others: Challenges For A Sustainable Peace in Caquetá, Colombia - Fontecha-Tirado, Maria M (Consilience, 2018)
In the Amazonian department of Caquetá (Colombia), considered a Revolutionary Armed Forces of Colombia (FARC) stronghold, 300 families are currently challenged with implementing the peace agreement in their territory while also navigating the road to sustainable development. This process entails trusting others, collaborating, and making decisions about health and education services, environmental problems, economic issues, and even aspects of everyday life. The Paisajes Conectados program is focused on reducing deforestation and promoting sustainable development in two municipalities of Caquetá. Its mission is to build new skills and share knowledge within local communities in order to strengthen governance and participation. This paper presents the findings of a field practicum, developed with the objective of determining community perceptions of the Capacity Building and Governance Strategy implemented under the Paisajes Conectados program in the context of a transition from conflict to peace.